Pengaruh Lingkungan Kerja, Disiplin Kerja, Kompensasi, Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pabrik Beras Sampoerna Di Kotagajah, Kabupaten Lampung Tengah - Fitriani, Fitriani; Imantoro, Jati; Fuadin, Muhammad Ilham (Jurnal Manajemen DIVERSIFIKASI, 2023)
In a company's operating system, human resources are a very valuable company asset thatmust be managed properly by the company in order to make an optimal contribution. Thegrowth of the company's organization is very dependent on the productivity of the workforcein the company. The company's goals can be achieved if the performance provided meetspredetermined standards. Every organization or company will always try to improve theperformance of its employees in the hope that the company's goals will be achieved. Thisstudy aims to determine the effect of work environment, work discipline, compensation, andjob satisfaction on the performance of Sampoerna rice factory employees in Kotagajah. Theresearch method used is quantitative research, namely questionnaires or interviews. In thisresearch , the analytical technique used is multiple linear regression analysis to determinethe dependent and independent variables with the help of a computer program , namely SPSS26. The results of the study achieved that the variables of work environment, work discipline,compensation, and job satisfaction had a positive and significant effect on employeeperformance.